Effectiveness Of Decoction Of Ciplukan Plants (Physalis Angulata L) As Anti-Hypercholesterolemia In Rundeng Village, Johan Pahlawan District, West Aceh Regency - Syachyan, Nur; Nasution, Nurromsyah; Febrianti, Yurica; Aulia, Yulfa; Aida, Nurul Siti (Journal of Midwifery and Nursing, 2024)
Hypercholesterolemia has become a health problem in developing countries such as Europe, America and Southeast Asia. Hypercholesterolemia can be reduced with non-pharmacological therapy, one of which is by consuming a decoction of the Ciplukan Plant (Physalis Angulata L). The Ciplukan plant (Physalis angulata L) contains many secondary metabolite compounds, namely flavonoids and phenolics such as physalin, physagulin, beta-carotene, myricetin, oleanolic acid and quercetin which have very good effectiveness in reducing plasma lipid levels in sufferers of hypercholesterolemia. The aim of this research was to determine the effectiveness of a decoction of the Ciplukan plant (Physalis Angulata L) as an antihypercholesterolemia in Rundeng Village, Johan Pahlawan District, West Aceh Regency. The design used was "Quasi experimental pre test and post test one group". Simple in this research were all hypercholesterol sufferers in Rundeng village, totaling 40 people, using the Willcoxon test. Drink a decoction of the Ciplukan Plant (Physalis Angulata L) three times a week for 1 month. The results of the research show that there is effectiveness of a decoction of the Ciplukan Plant (Physalis Angulata L) as antihypercholesterolemia in Rundeng Village, Johan Pahlawan District, West Aceh Regency with a P-Value of 0.000 > ? 0.05. A decoction of the Ciplukan Plant (Physalis Angulata L) as an anti-hypercholesterolemia can be used as a non-pharmacological therapy to reduce cholesterol levels.